Cultural Revolutions Reason Versus Culture in Philosophy, Politics, and Jihad - Cahoone, Lawrence E. (Penn State University Press, 2005)
Cultural Revolutions argues that reason itself is cultural, but no less reasonable for it. Lawrence Cahoone systematically defines culture and gauges the consequences of the ineradicably cultural nature of cognition and action, yet argues that none of this implies relativism. Cahoone offers a definition of culture as teleologically organized practices, artifacts, and narratives and analyzes the notion of cultural membership in relation to race, ethnicity, and primordialism. He provides a theory of culture's role in how we form our sense of reality and argues that the proper conception of culture dissolves the problem of cultural relativism. Applying this perspective to Islamic fundamentalism, Cahoone identifies its conflict with the West as representing the break between two of three historically distinctive forms of reason. Rather than being irrational, he shows, fundamentalism embodies a rationality only recently devalued, but not entirely abandoned by the West.
Description based on print version record.
KU Select 2016 Backlist Collection
Keywords: Philosophy / Epistemology; Philosophy; Electronic books